Analisis Overclaim Marketing dalam Membangun Kepercayaan Konsumen pada Produk Daviena Skincare - Keysi Rahmawati, Keysi Rahmawati; Erwin Permana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Marketing is the backbone of a business’s existence. Various ideas, creativity, and innovations in marketing continue to evolve in different forms. To attract a large number of consumers, some businesses engage in overclaim marketing. While this strategy may bring positive outcomes for some companies, it can also have negative consequences for others. One brand that has practiced overclaim marketing is Daviena Skincare. This study aims to analyze the impact of overclaim marketing on consumer trust in Daviena Skincare products. The research was conducted using a qualitative descriptive approach, with data obtained through digital tracing and observation. The findings indicate that overclaim marketing in the skincare industry, as practiced by Daviena Skincare, has negatively affected consumer trust. The overclaims identified include promises of instant results, false claims about premium ingredients, and unverified testimonials. An investigation by Doctor Detective revealed significant discrepancies between marketing claims and the actual product composition, such as Niacinamide, which was advertised at 10% but was not detected in laboratory tests. These findings contradict the marketed product benefits, leading to consumer disappointment and decreased brand loyalty. This phenomenon underscores the urgency for brands to be more transparent and ethical in their marketing strategies. Therefore, overclaim marketing practices must be eliminated to maintain the integrity of the industry and protect consumers’ rights to accurate information and products that align with their claims.